Detection of human papillomavirus in vulval carcinoma using semi-nested PCR and restriction enzyme typing: a rapid and sensitive technique. Issue 4 (August 1996) - Cartwright, N H; Cassia, L J Sant; Easton, A J; Morris, A G
Abstract : Aims —To develop a highly sensitive technique for the reliable detection and typing of human papillomavirus (HPV) DNA in clinical tissue. Methods —A two step, semi-nested PCR was used with primers spanning the L1 region of the HPV genome and capable of detecting HPV DNA of all known HPV types. The clinical samples were typed by digestion of the 412 base pair PCR product with Rsa I, generating unique fragments for each HPV type. Thirteen samples were screened by this method, including nine vulval carcinoma samples and four wart samples from the penis and vulva. Results —Experiments using DNA extracted from HPV DNA positive cell lines—that is, CaSki (HPV type 16) and HeLa (HPV type 18) established that the technique could detect as few as 50 HPV copies and that the predicted Rsa I fragments from HPV types 16 and 18 were generated. The predicted 412 base pair fragment was observed for all 13 clinical samples subjected to semi-nested PCR. Rsa I digestion of the product of the second round of PCR permitted the positive identification of the HPV type in most cases. Conclusions —This technique provides an effective and rapid means of detecting HPV DNA, in most cases providing the HPV type. High risk HPV types were always detected in the nine vulval carcinoma samples analysed. The amount of tissue available from the biopsy specimens was small, confirming the sensitivity of the method.